An in vitro study of apoptosis in pancreatic cancer cells by high-intensity nanosecond pulses - N. Pausawasdi (2018)
This paper reports the unique apoptotic responses of human pancreatic cancer cells (Panc-I) induced by nsPEF systems. In vitro experiments were carried out using laboratory-assembled apparatus, serving the cells with 10-ns and 500-ns high-intensity pulses. Our data suggested that the apoptotic effects of nsPEF on Panc-I cells are pulse characteristics dependent. In addition, both long pulse duration and post treatment period are required to initiate the apoptosis demonstrated by a maximal increase in activation of caspases-3/7 activities of 50% (p < 0:05) at 24 h after 500-ns nsPEF treatment. The slow progression rate of apoptosis induced by nsPEF appears to be a unique property of Panc-I cells when compared to other mammalian cells. nsPEF-induced apoptosis in Panc-I cells may involve multiple mechanisms but at least in part due to intrinsic pathway and activation of caspase signaling.